Growth and andrographolide content of Andrographis paniculata grown on different growing media and media water status - Muslianie Md Isa
Andrographis paniculata (Hempedu bumi) is a medicinal plant that widely distributed in a variety of habitats throughout the world. It has a wide range of medicinal and pharmacological application. This study is aims to investigate the effect of different growing media and media water status on the growth and bioactive compound (andrographolide) content of A: paniculata. An experiment was conducted at the greenhouse Institute of Sustainable Agrotechnology (INSAT), Universiti Malaysia Perlis (UniMAP) during April 2012 to February 2013. The experiment was laid out in randomized complete block design (RCBD) of two factors consisting of 9 treatments with 3 replications. Each replication consisted of 24 plants. Three different growing media were applied, namely compost, topsoil and sand. The growing media were combined in different ratios (1:2:3, 2:2:1 and 3:2:1) with three different soil water potential; -20 kPa (high), -60 kPa (medium) and -100 kPa (low). Soil water potential in each growing media was measured by gypsum block. The crops were harvested 115 Days after transplanting at maturity. Analysis of andrographolide content in each treatment was analyzed by using High Performance Liquid Chromatography (HPLC) for each of plant parts (leaves, stems and roots). Generally, there were significant increases (P <0.05) in plant height, number of leaves per plant, number of branches per plant, diameter of stem, leaves dry weight, stem dry weight, root dry weight, total dry weight per plant and andrographolide content in each plant part of plants that had been planted in media mixture contained compost: topsoil: sand (3:2:1) under high soil water potential compared to other treatments. However, the root to shoot ratio of plant that had been planted on the lowest compost ratio under low soil water potential produced the highest ratio compared to other treatments. Significant interaction effects between growing media and soil water potential were observed for all parameters. The study concluded that the application of potting mixture that contained compost, topsoil and sand in a ratio 3:2:1 with well water supplied are recommended for A. paniculata grown under greenhouse condition.